The social preferences of the native inhabitants, and the decision how many asylum seekers to admit - Oded Stark; Marcin Jakubek; Krzysztof Szczygielski (University of Tübingen, Faculty of Economics and Social Sciences, 2019)
We consider a tax-funded policy of admitting and integrating asylum seekers in a country in which the incomes of the native inhabitants are differentiated; for the sake of simplicity, we assume that there are just two groups of native inhabitants: high-income natives and low-income natives. As a consequence of their social preferences, the latter experience disutility caused by relative deprivation. Because integrating the asylum seekers into the mainstream labor force and thereby into the income distribution of the native population 'from below' reduces the relative deprivation of the low-income natives, admitting and integrating asylum seekers can be socially beneficial. We derive the optimal number of asylum seekers by maximizing the natives' social welfare function that incorporates these considerations. We find that as long as the cost of admission and integration is not exceptionally high, this number is strictly positive. We then address the issue of how to distribute a given number of asylum seekers among several receiving countries. We find that, rather than allocating the asylum seekers in proportion to the population of each country, aggregate welfare will be maximized through an allocation that is increasing in the within-country difference between the incomes of the high-income natives and the low-income natives. Additionally, we formulate conditions under which admission of the optimal number of asylum seekers is socially preferable to a direct transfer of income from high-income natives to low-income natives.
urn:nbn:de:bsz:21-dspace-952054
Keywords: D60; F02; F22; I31; J61; J68; 330; Admission and integration of asylum seekers; Social preferences; Relative deprivation; Tax-funded integration policy; Maximization of social welfare